2011
DOI: 10.2225/vol14-issue5-fulltext-9
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and initial pH on biohydrogen production from palm oil mill effluent: long-term evaluation and microbial community analysis

Abstract: Anaerobic sludge from palm oil mill effluent (POME) treatment plant was used as a source of inocula for the conversion of POME into hydrogen. Optimization of temperature and initial pH for biohydrogen production from POME was investigated by response surface methodology. Temperature of 60ºC and initial pHof 5.5 was optimized for anaerobic microflora which gave a maximum hydrogen production of 4820 ml H2/l-POME corresponding to hydrogen yield of 243 ml H2/g-sugar. Total sugar consumption and chemical oxygen dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(16 citation statements)
references
References 33 publications
3
11
2
Order By: Relevance
“…The hydrogen production at HRT of 2 and 1 day were 4.2 and 4.0 L H 2 /L-POME, respectively. This hydrogen production was comparable with those of previous report; 4.7 L H 2 /L-POME [32], 4.8 L H 2 /L-POME [20] and 4 L H 2 /L-POME [33]. The phenol removal efficiency at HRT 2 and 1 day were 92% and 85%, respectively (Fig.…”
Section: 3supporting
confidence: 91%
See 4 more Smart Citations
“…The hydrogen production at HRT of 2 and 1 day were 4.2 and 4.0 L H 2 /L-POME, respectively. This hydrogen production was comparable with those of previous report; 4.7 L H 2 /L-POME [32], 4.8 L H 2 /L-POME [20] and 4 L H 2 /L-POME [33]. The phenol removal efficiency at HRT 2 and 1 day were 92% and 85%, respectively (Fig.…”
Section: 3supporting
confidence: 91%
“…Khanal et al [28] reported that pH is a pivotal parameter for biohydrogen production and suggested that pH 5.5 was the optimum initial pH for hydrogen production. O-Thong et al [20] also reported that pH 5.5 and temperature of 60 C were optimum for hydrogen production from POME by Thermoanaerobacterium-rich sludge. Effect of phenol concentration on Thermoanaerobacteriumrich sludge was test in POME adjusted pH to 5.5 and augmenting phenol at 100e1000 mg/L.…”
Section: Hydrogen Production At Various Concentration Of Phenolmentioning
confidence: 96%
See 3 more Smart Citations